Analysis Of Service Quality On Internal Disease Poly Patients' Interest In Returning Patients At Gambiran Hospital, Kediri City - Mochamad Ridwan; Panca Radono; Titin Susanti; Endra Widiyanto (Journal of Hospital Management and Services, 2024)
Background. Quality service provides satisfaction to customers, which ultimately results in customers making repeat use/interest in repeat visits and recommending the health service to others. Quality health services include five dimensions of quality, namely tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee) and empathy (empathy). The aim of the research is to analyze the quality of service on the interest in repeat visits of internal medicine polyclinic patients at Gambiran Regional Hospital, Kediri City. Research methods. Quantitative research uses a cross-sectional approach (cross sectional study). The population in the study were all new internal medicine patients who visited the Gambiran Regional Hospital, Kediri City with a sample of 105 respondents. The sampling technique uses purposive sampling technique. The independent variable is service quality (tangible (physical evidence), reliability, responsiveness, assurance and empathy) and the dependent variable is interest in repeat visits. Data collection techniques used questionnaires and were analyzed using chi-square. Research result. The chi square test results for the dimension of physical evidence (tangible) are PR=2.221, 95%CI =1.078-4.533, p-value = 0.037 and the dimension of reliability (reliability) is PR=5.903, 95%CI =2.207-15.785, p-value = 0.037, which means that there is a relationship between physical evidence (tangible) and reliability (reliability) with the interest in revisiting internal medicine polyclinic patients at Gambiran Regional Hospital, Kediri City. The dimensions of responsiveness (responsiveness), assurance (assurance) and empathy (empathy) have no relationship with interest in revisiting internal medicine polyclinic patients at Gambiran Regional Hospital, Kediri City (p-value ≥ 0.05). Conclusion. There is a relationship between the quality of service in the tangible dimension (physical evidence) and reliability (reliability) on the interest in repeat visits of internal medicine polyclinic patients at Gambiran Regional Hospital, Kediri City. Therefore, there is a need for synergy among one work unit to increase interest in repeat visits.